(untitled) (Research, Society and Development, 2023)
Cancer is considered a disease that presents the disordered growth of cells that invade tissues and organs, and can spread to other regions of the body. These cells tend to be very aggressive and uncontrollable, leading to the formation of tumors, accumulation of cancer cells or malignant neoplasms. In this line of understanding, the objective of this study was to point out which palliative care physiotherapy can perform in cancer patients. This is an integrative literature review research. The research sources were obtained through a bibliographic survey, using articles published in the following databases: BVS Brasil, National Library of Medicine (MEDLINE), and Scientific Electronic Library Online (SCIELO). The results point to greater awareness and knowledge on the part of professional physiotherapists about the temporary identification of palliative needs in oncology, focusing the therapeutic plan on the needs of these patients. It is concluded that the early identification of the palliative need provides a better quality of life for patients and relatives of cancer patients.